Phenotypic spectrum of GABRA1: From generalized epilepsies to severe epileptic encephalopathies. (13th September 2016) - Johannesen, Katrine; Marini, Carla; Pfeffer, Siona; Møller, Rikke S.; Dorn, Thomas; Niturad, Christina; Gardella, Elena; Weber, Yvonne; Søndergård, Marianne; Hjalgrim, Helle; Nikanorova, Mariana; Becker, Felicitas; et al.
Abstract : Objective: To delineate phenotypic heterogeneity, we describe the clinical features of a cohort of patients with GABRA1 gene mutations. Methods: Patients with GABRA1 mutations were ascertained through an international collaboration. Clinical, EEG, and genetic data were collected. Functional analysis of 4 selected mutations was performed using the Xenopus laevis oocyte expression system. Results: The study included 16 novel probands and 3 additional family members with a disease-causing mutation in the GABRA1 gene. The phenotypic spectrum varied from unspecified epilepsy (1), juvenile myoclonic epilepsy (2), photosensitive idiopathic generalized epilepsy (1), and generalized epilepsy with febrile seizures plus (1) to severe epileptic encephalopathies (11). In the epileptic encephalopathy group, the patients had seizures beginning between the first day of life and 15 months, with a mean of 7 months. Predominant seizure types in all patients were tonic-clonic in 9 participants (56%) and myoclonic seizures in 5 (31%). EEG showed a generalized photoparoxysmal response in 6 patients (37%). Four selected mutations studied functionally revealed a loss of function, without a clear genotype–phenotype correlation. Conclusions: GABRA1 mutations make a significant contribution to the genetic etiology of both benign and severe epilepsy syndromes. Myoclonic and tonic-clonic seizures with pathologic response to photic stimulation are common and shared features in both mild and severe phenotypes.